2014
DOI: 10.1089/ars.2013.5363
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Kidney Health and Disease

Abstract: Significance: Autophagy is emerging as an important pathway in many biological processes and diseases. This review summarizes the current progress on the role of autophagy in renal physiology and pathology. Recent Advances: Studies from renal cells in culture, human kidney tissues, and experimental animal models implicate that autophagy regulates many critical aspects of normal and disease conditions in the kidney, such as diabetic nephropathy and other glomerular diseases, tubular injuries, kidney development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 106 publications
(180 reference statements)
0
88
0
1
Order By: Relevance
“…It has been reported that reabsorption of albuminuria elicits autophagy in the proximal tubular epithelium as a renoprotective process, and proteinuria-induced autophagy was suppressed via hyper-activation of mTORC1 under hyperglycaemic conditions. Previous studies have showed that rapamycin treatment can ameliorate renal hypotrophy in a mouse model of diabetes via inhibition of mTORC1 [11,15,[23][24][25]. In addition, mTOR signaling inhibition might be associated with renal function reserve in chronic diabetic kidney disease (CDKD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that reabsorption of albuminuria elicits autophagy in the proximal tubular epithelium as a renoprotective process, and proteinuria-induced autophagy was suppressed via hyper-activation of mTORC1 under hyperglycaemic conditions. Previous studies have showed that rapamycin treatment can ameliorate renal hypotrophy in a mouse model of diabetes via inhibition of mTORC1 [11,15,[23][24][25]. In addition, mTOR signaling inhibition might be associated with renal function reserve in chronic diabetic kidney disease (CDKD).…”
Section: Discussionmentioning
confidence: 99%
“…Of the three mechanisms, macroautophagy is the most predominant and complicated intracellular process and is often simply referred to as autophagy. Autophagy initiates with the formation of autophagophores, and the Beclin1-interacting complex that consists of Beclin1 and BCL-2 family proteins is required for the initiation process [21][22][23]. Autophagophores elongate and expand, and the elongation requires two ubiquitin-like conjugation systems: the ATG5-ATG12 conjugation system and the microtubule-associated protein light chain 3 (LC3/ATG8) conjugation system.…”
Section: New Players: Autophagymentioning
confidence: 99%
“…88,89 It was previously reported that mTOR signaling is activated in PKD, and rapamycin was identified as an effective therapeutic agent against cystogenesis in rat and mice PKD models. However, rapamycin (everolimus) was not a successful treatment in clinical trials with PKD patients.…”
Section: Autophagy and Ciliummentioning
confidence: 99%
“…However, rapamycin (everolimus) was not a successful treatment in clinical trials with PKD patients. [88][89][90] The regulation of the mTOR pathway is crucial during cystic development. Epithelial cells lining the cysts expressing mutated PC1 protein have increased levels of cell proliferation and abnormally activated mTOR signaling because of a disrupted interaction between PC1 and tuberin, a product of TSC2 gene, which controls mTOR activity.…”
Section: Autophagy and Ciliummentioning
confidence: 99%
“…Progressive autophagy dysfunction can stimulate apoptosis and degeneration in renal cells in IR-induced AKI animals [7]. Thus, the enrichment effects of ω3-PUFAs on autophagy were investigated.…”
Section: Effects Of Endogenous ω3-pufas On Autophagy Fluxmentioning
confidence: 99%